WEB APPLICATIONS OF WOMEN DRESS MOSLEM WITH MACROMEDIA DREAMWEAVER 8.0 - Susanti Susanti (Jurnal Sistem Informasi, 2007)
Muslim women fashion website is a World Wide Web application that contains information about accessing an address that is packed into a form that interesting and interactive. Using Macromedia Dreamweaver 8, this application is a combination of elements that web pages of text, images and animation are summarized as one of the expected application form and easy to use by users and made it interesting for these applications. By simply clicking on the text of the menu choices available, the user or users to directly obtain information quickly.